Risk assessment of power system oscillation instability based on geomagnetic storm events in the 24th solar cycle - Zezhong Wang (Wiley, 2022)
Abstract When studying the harm of geomagnetic storms to the power system, the focus is often placed on the influence of transformers reactive power loss (GIC‐Q) caused by geomagnetic induced current (GIC) on voltage fluctuation. GIC‐Q, as a reactive load, can cause power flow changes, and the small disturbance stability is affected by the power flow distribution before disturbance, so GIC‐Q connects geomagnetic storms with small disturbance stability. In this study, the probability distribution function of induced geoelectric fields is established, and the sample data is obtained by sampling. Combined with the GIC benchmark network model, multiple sets of GIC‐Q in each substation are calculated and added to the system one by one to study the influence of geomagnetic storms on the oscillation characteristic parameters and establish the risk index of small disturbance instability. The result shows that the risk index value of oscillation instability in the occurrence of geomagnetic storms increases both in the AC system and the AC/DC hybrid system, but the increased range of risk value of local oscillation instability decreases with the addition of DC systems. The research results can provide a reference for evaluating the influence of geomagnetic storms on the stable operation of power systems.